Correlation studies between physical properties and concentration of voids entrenched in V2O5 mixed lead bismuth silicate glass system by means of positron annihilation spectroscopy. (March 2020) - Annapurna, T.; Kostrzewa, M.; Siva Sesha Reddy, A.; Ingram, A.; Ashok, J.; Ravi Kumar, V.; Veeraiah, N.
Abstract: In this investigation we have estimated the fraction of free volume defects and also their size (to the nanoscale) entrenched in V2 O5 doped PbO added Bi2 O3 –SiO2 glass system (by means of positron annihilation spectroscopy (PAS) studies) with a view to understand the influence of such defects on several physical properties of this glass system. The glasses of the chemical composition viz., 30PbO–5Bi2 O3 ‒ (65- x ) SiO2 : x V2 O5 (0 ≤ x ≤ 0.6, insteps of 0.1) are used in this study. Glasses were prepared by traditional melt quenching technique. PAS studies were perormed using 22 Na (0.1 MBq) positron radioactive source. Positron annihilation lifetime is found to be significantly affected by the concentrations of V2 O5 dopant. The third component I 3 of positrons is found to be feeble in all the glasses. For this reason, initially, we have used a simple two component positron trapping model (ignoring the third component) to calculate annihilation parameters viz., the bulk average positron lifetime (τb ), positron trapping rate in defect (κd ), fraction of trapped positrons (η), the average lifetime for all the positrons (τavg ) and defect-related time (τd ). The calculations were repeated with three component positron model. The results of positron annihilation studies have indicated that concentration of free volume nano sized defects, the fraction ( f v ) of volume defects and their radius ( R ) are the lowest for the glass V3 . Such minimal value of defect concentration is ascribed to dominant existence of vanadium ions in V 5+ valence state that involves in glass network forming with VO5 structural units. Whereas, the observed increased value of f v with increase of V2 O5 from 0.3 to 0.6 mol% is attributed to growing concentration of vanadyl complexes (VO) 2+ that have acted as modifiers. Quantitative information obtained on dependence of concentration of free volume imperfections on V2 O5 content in the studied glass is observed to be in good agreement with the inferences drawn from several macroscopic properties that include electrical properties reported earlier. Highlights: PbO–Bi2 O3 –SiO2 glasses doped with different concentrations of V2 O5 were synthesized. Concentration of free volume defects trapped in glasses estimated by PAS technique. Radius of voids is found to be the lowest in the glass doped with 0.3 mol% of V2 O5 . Change in free volume defect concentration is correlated with VO 2+ ion concentration.